Effect of Pr doping on the properties of Bi0.5−xPrxCa0.5MnO3 (0≤x≤0.50) manganites. Issue 3 (April 2015) - Ade, Ramesh; Singh, R.
Abstract: In this work, we report the temperature dependent electron spin resonance (ESR) and magnetization ( M ) studies of Bi0.5− x Pr x Ca0.5 MnO3 (0≤ x ≤0.50) manganites synthesized by the sol–gel method. The x-ray diffraction (XRD) data analysis indicates that 6s 2 lone pair character of Bi 3+ ions is dominant in undoped sample and it changes to constrained type when doped with Pr at Bi site. The charge ordering temperature ( T CO ) decreases from 327 K to 250 K as x increases from 0 to 0.15. The T CO value remains at 250 K with further increase in Pr content. The nonlinear behavior of ESR signal linewidth (Δ H ) as a function of temperature above T CO, observed for doped samples is an indication of strengthening of electron spin–lattice interactions. The sharp rise in M value below 45 K for undoped sample and below 115 K for doped samples is characteristic of ferromagnetic (FM)-cluster glass behavior. The results are discussed in view of the effects of Pr doping on 6s 2 lone pair character of Bi 3+ ions, disorder in the system and changes in the surface/volume ratio of the grains.